The Role of Traditional Institutions in Preserving the Al-Barzanji Tradition - Dewi, Irlina; Utari, Yuni Dhea (Al-Jadwa: Jurnal Studi Islam, 2024)
The process of preserving culture in indigenous communities cannot be separated from the important role of traditional institutions. The role of traditional institutions has the potential to determine the behavior of indigenous peoples in carrying out their traditional traditions or not. The aim of this research is to analyze the role of traditional institutions in preserving the tradition of al-berzanji, a case study of teenagers in Bengkalis District. The type of research used is field research, while the research approach is descriptive qualitative research. The data collection methods used were interviews, literature study and documentation. The results of the research show that the role of traditional institutions in preserving the al-berzanji tradition among teenagers in Bengkalis District has not been achieved (not yet realized). This is because this institution is still hampered by several obstacles in carrying out its roles, duties and functions optimally. The inhibiting factors include: Limited budget owned by Malay traditional institutions in Bengkalis District, minimal attention from related agencies, low regeneration efforts from traditional figures and leaders, lack of interest and concern from teenagers to learn about their customs and culture, and the large influence of modernization and technological progress. which is not balanced with understanding and cultivation of local culture